Development of System Dynamics Model for General Practitioner Workforce Forecasting in Kazakhstan - B. Koichubekov; A. Kharin; M. Sorokina; I. Korshukov; B. Omarkulov (Recent Updates in Disease and Health Research Vol. 2, 2024)
Background: It has been established that primary health care is a very effective and efficient means of addressing the primary causes and dangers of poor health and well-being today, as well as addressing the new issues that will endanger health and well-being in the future. Human resources for health are one the building blocks of health systems, and the types and the number of healthcare providers needed in each health system are closely linked to how healthcare is organized in each country. Aim: In our study, we used the System Dynamics approach to develop a model for the population and General Practitioner workforce to include multiple inputs and their relationships in the equations for each stock and flow. Methods: We propose a model which takes into consideration the dynamic nature of the system, the feedbacks that occur naturally in it and the possible policy levers that can affect it. The model presents a systematic decision support tool for the regulators, enabling testing of the long-term effects of various policies on the health care gap. Three scenarios were examined for forecasting primary health care personnel resources. The base year for forecasting was 2018, and the modeling was carried out until 2030. Results: All of three scenarios indicate that with the current number of graduated General Practitioners, the shortage of primary care physicians will be exacerbated. In general, the shortage can reach more than 2,000 on a population of 18.3 million (2018). The model is as realistic as all the given input parameters are realistic. The problem of obtaining objective data on the healthcare workforce is the greatest limitation in our workforce planning model implementations. Conclusion: The projected shortage of doctors in the primary health care system requires special attention to human resource planning. Only one third of medical graduates in Kazakhstan go to work in the primary health care system. The government needs to develop measures to stimulate and support young medical doctors to become general practitioners.